Self-Productivity and Complementarities in Human Development: Evidence from MARS - Manfred Laucht; Katja Coneus; Dorothea Blomeyer; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper investigates the role of self-productivity and home resources in capability formation from infancy to adolescence. In addition, we study the complementarities between basic cognitive, motor and noncognitive abilities and social as well as academic achievement. Our data are taken from the Mannheim Study of Children at Risk (MARS), an epidemiological cohort study following the long-term outcome of early risk factors. Results indicate that initial risk conditions cumulate and that differences in basic abilities increase during development. Self-productivity rises in the developmental process and complementarities are evident. Noncognitive abilities promote cognitive abilities and social achievement. There is remarkable stability in the distribution of the economic and socio-emotional home resources during the early life cycle. This is presumably a major reason for the evolution of inequality in human development.
Keywords: I12; D87; I21; J13; 330; Initial Conditions; Intelligence; Persistence; Home Resources; Social Competencies; School Achievement; Kinder; Persönlichkeitspsychologie; Bildungsinvestition; Familiensoziologie; Kognition; Bildungsniveau; Deutschland